Report from the International Scientific Conference DLCC2017 in Cieszyn and Katowice, Poland, 16–17 October 2017 - Smyrnova-Trybulska, Eugenia; Stec, Maria; Studenska, Anna (International Journal of Research in E-learning, 2017)
The theme of the 9th edition of the International Scientific Conference DLCC2017: Theoretical and Practical Aspects of Distance Learning (www.dlcc.us.edu.pl) was “Effective development of teacher’s skills in ICT and e-learning”; the conference also included reports from the IRNet project. The conference was held on 16–17 October 2017 in Cieszyn and Katowice. It was organised by the Faculty of Ethnology and Educational Science at the University of Silesia in Cieszyn. The co-organisers were: the University of Ostrava (the Czech Republic); the Silesian University in Opava (the Czech Republic); the Constantine Philosopher University in Nitra (Slovakia); the Twente University (the Netherlands); the University of Extremadura (Spain); the Curtin University in Perth (Australia); the Borys Grinchenko Kiev University (Ukraine); the Herzen State Pedagogical University of Russia (Russia); the Dneprodzerzhinsk State Technical University (Ukraine); Ministry of Science and Higher Education, Poland; Polish Pedagogical Association, Branch in Cieszyn; Polish Scientific Association of Internet Education; and IADIS – International Association for Development of the Information Society.